The Influence of Using the Discovery Learning Learning Model Assisted by the Quizizz Application Media on the Learning Outcomes - Esti Retnaningrum; Joko Pamungkas (Jurnal Penelitian Pendidikan IPA, 2024)
The research aims to examine the influence of using learning using the discovery learning learning model assisted by the Quizizz application on the learning outcomes of Class VI students on the topic of Ecosystem Balance. The research was carried out at SD Negeri 2 Keputran on class VI students. The sampling technique uses a purposive area sampling method. The research used a quasi-experimental design with data collection techniques through post-tests in the form of multiple choice questions and descriptions, observation, documentation and interviews. The data obtained was analyzed using statistical tests which included normality tests, data analysis using the Paired Samples t-Test. Based on the Validity Test, the results show r = 0.829 α >(0.05) so that all question items show valid results. Reliability test if the α value > 0.734 the value is reliable. Then the results of the normality test value of learning outcomes are 0.562 > α (0.05) exceeding the significant value, so the variable values ​​are normally distributed, followed by using the Paired Sample t-Test test, the results of the t-test results are learning outcomes at a sig value of 0.00 < α (0.05) then reject H0. So it can be concluded that there is an influence of the use of learning using the discovery learning learning model assisted by the Quizizz Application on the Learning Outcomes of Class VI Students on Ecosystem Balance Material